2018
DOI: 10.3390/su10093186
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Health Systems in the European Union: Outcomes and Fiscal Sustainability

Abstract: Healthcare systems aim to provide access to good quality care, while ensuring equity and solidarity. The fiscal sustainability of healthcare systems has become a matter of concern in recent European Union (EU) debates, considering the ever increasing need for adequate healthcare determined by factors such as aging population, investments in technology and infrastructure, medical products and wages. Our paper seeks to measure the health system performances of the EU countries by building up a composite index, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…Countries with high national competitiveness and high expenditure on health also can afford to invest in safety management in the work environment and provide healthcare for workers. Popescu et al showed a positive correlation between healthcare expenditure and health index (the composite of health status, medical service supply and health indicators related to the labour marker) among the European Union countries [35].…”
Section: Discussionmentioning
confidence: 99%
“…Countries with high national competitiveness and high expenditure on health also can afford to invest in safety management in the work environment and provide healthcare for workers. Popescu et al showed a positive correlation between healthcare expenditure and health index (the composite of health status, medical service supply and health indicators related to the labour marker) among the European Union countries [35].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the sustainability of health care systems consistently shows that the future path of morbidity is a key determinant of future health care demand and funding requirements. 105 Previous projections by the Health Foundation and Institute for Fiscal Studies (IFS) showed that for 18 conditions the probability of admission standardised for age had increased by 57% between 2007/08 and 2017/18, with the greatest increase for people with multiple conditions -a growing group in the population. The analysis found that if these trends continued for the next decade, long-term conditions would have as great an impact on hospital activity as ageing.…”
Section: A Systematic National Projection Of Future Trends In Morbidimentioning
confidence: 99%
“…In addition, the provision of health care should occur without contributing to influencing financial strain, poverty, or to social and health inequity outcomes for individuals and population groups. 6 However, the COVID-19 pandemic has exposed the failures associated with the type of health care systems prevailing in some countries. Within this context, we can establish a contrast between how the health care systems in Europe and the US responded, and still do today, as the task of controlling the infection is still unfolding.…”
Section: Introductionmentioning
confidence: 99%
“…), European countries have been able to provide universal health care to their citizens during the pandemic. 6 , 7 By contrast in USA, the Affordable Care Act (ACA) was enacted in 2010 to establish “shared responsibility” between the government, employers, and individuals with the purpose to ensure that all USA citizens have access to affordable and good-quality health insurance. However, as compared to other developed nations, the USA health care system is fragmented; with a myriad of various private and public sources with gaps in rates of insured people across the country.…”
Section: Introductionmentioning
confidence: 99%